Novel linear polymers able to inhibit bacterial quorum sensing - Cavaleiro, Eliana; Duarte, Ana Sofia; Esteves, Ana Cristina; Correia, António; Whitcombe, Michael J.; Piletska, Elena V.; Piletsky, Sergey A.; Chianella, Iva (Wiley, 2015)
Bacterial phenotypes, such as biofilm formation, antibiotic resistance and virulence expression, are associated with quorum sensing. Quorum sensing is a density-dependent regulatory system of gene expression controlled by specific signal molecules, such as N-acyl homoserine lactones (AHLs), produced and released by bacteria. This study reports the development of linear polymers capable to attenuate quorum sensing by adsorption of AHLs. Linear polymers were synthesized using MMA as backbone monomer and methacrylic acid and itaconic acid as functional monomers. Two different quorum sensing-controlled phenotypes, Vibrio fischeri bioluminescence and Aeromonas hydrophila biofilm formation, were evaluated to test the polymers' efficiency. Results showed that both phenotypes were significantly affected by the polymers, with the itaconic acid-containing material being more effective than the methacrylic acid one. The polymer inhibitory effects were reverted by the addition of lactones, confirming attenuation of quorum sensing through sequestration of signal molecules. The polymers also showed no cytotoxicity when tested using a mammalian cell line.